2006
DOI: 10.1111/j.1572-0241.2005.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of the Chemokine Fractalkine in Crohn's Disease and Association of the Fractalkine Receptor T280M Polymorphism with a Fibrostenosing Disease Phenotype

Abstract: The expression of the chemokine fractalkine is upregulated by proinflammatory cytokines and enhanced in inflamed CD lesions. The CX3CR1 T280M polymorphism appears to influence CD phenotype and localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 33 publications
2
81
0
Order By: Relevance
“…28 In addition, we demonstrated that the T280M polymorphism in the CX3CR1 gene, which encodes the receptor for the chemokine fractalkine, is also associated with ileal disease. 18 This is consistent with the essential role of CX3CR1-expressing dendritic cells in the luminal sampling of bacteria in the terminal ileum which we demonstrated in a previous study. 42 These observations suggest that genetic variants, which are associated with deficits in the recognition of the intestinal bacteria or bacterial products, are associated with a predominant ileal disease location, triggered by the 10 3 -to 10 4 -fold increase of microbial density from the terminal ileum to the colon.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…28 In addition, we demonstrated that the T280M polymorphism in the CX3CR1 gene, which encodes the receptor for the chemokine fractalkine, is also associated with ileal disease. 18 This is consistent with the essential role of CX3CR1-expressing dendritic cells in the luminal sampling of bacteria in the terminal ileum which we demonstrated in a previous study. 42 These observations suggest that genetic variants, which are associated with deficits in the recognition of the intestinal bacteria or bacterial products, are associated with a predominant ileal disease location, triggered by the 10 3 -to 10 4 -fold increase of microbial density from the terminal ileum to the colon.…”
Section: Discussionsupporting
confidence: 74%
“…45 However, functional studies are needed to analyse if the +1059 G/C polymorphism leads to an impaired recognition of bacteria by CRP which would explain a similar CD phenotype as observed for the 1007fs CARD15 variant 28 and the T280M CX3CR1 genotype. 18 The influence of the CRP +1059G/C polymorphism on CD has not been studied so far. Here, we demonstrate that the presence of a C allele, particularly in male patients and CD patients with a CDAI < 150, is associated with lower serum CRP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern of expression mirrors that found in epithelial cells of biliary ductules (44) but differs markedly from that of intestinal epithelial cells, where CX 3 CL1 largely is expressed in the basolateral membrane and in regions of intercellular contact (45,46). In the intestine, as in the kidney, expression of CX 3 CL1 is highly enhanced in disease states that are marked by active inflammation (14,45,47).…”
Section: Discussionmentioning
confidence: 62%
“…For example, CX3CR1 polymorphisms have been implicated in conditions such as Crohn's disease, multiple sclerosis, and bronchiolitis among Caucasians [25][26][27]. Further downplaying the possible role of CX3CR1 genetic polymorphism on HIV infection, no significant differences in CX3CR1 745G>A genotype and allele frequencies between HIV EI and EU children were observed (Table 3).…”
Section: Chemokine Receptor Polymorphism and Their Association With Hmentioning
confidence: 83%